Business Groups in Emerging Markets - Financial Control and Sequential Investment - Christa Hainz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Business groups in emerging markets perform better than unaffiliated firms. One explanation is that business groups substitute some functions of missing institutions, for example, enforcing contracts. We investigate this by setting up a model where firms within the business group are connected to each other by a vertical production structure and an internal capital market. Thus, the business group's organizational mode and the financial structure allow a self-enforcing contract to be designed. Our model of a business group shows that only sequential investments can solve the ex post moral hazard problem. We also find that firms may prefer not to integrate.
urn:nbn:de:bvb:19-epub-13427-1
Keywords: G31; G32; G34; K49; L22; 330; Business groups; self-enforcing contract; institutions; internal capital market